DIVERSITAS SERANGGA PADA HUTAN TANAMAN MONOKULTUR DAN HUTAN HETEROGEN DENGAN METODE WINDOW TRAPS - Falahudin, Irham; Jasmi, Jasmi; Salmah, Siti; Dahelmi, Dahelmi (Universitas Islam Negeri Raden Fatah, 2012)
Insects are very important role in the ecosystem. Among these roles are: herbivory, predation, parasitism, decomposition, pollination, and so on. In addition the role of insects have also been used as an indicator species. Several recent studies indicate that insects exhibit responses that indicate the level of damage to forest habitats. To see how far the influence of the change will be seen flying insect diversity at both locations using window traps. This method was chosen because it will see the role of the flying insects that can be used as indicators of land use change on stratification of the tree which is in both locations expected goal in this study were 1) to determine the level of insect diversity at both forest sites 2) To determine the effect of changes in the forest insect conditions in each forest stratification. From this reseach it was found that the highest density levels are apparently heterogeneous forest there are 29 families 41 species and 119 individuals from arrest (day and night), while 22 families monocidture forest with 32 species and 98 individuals for whom the level of diversity among heterogeneous forest monoculture forests in monoculture forests range 2.14 <H <2.84. While in heterogeneous forests ranged from 2 <H <3 and the third similaty index was not significantly different strata.